The preliminary studies on protein profile in retained and not retained foetal membranes in heavy draft mares. Issue 12 (14th September 2019) - Wawrzykowski, Jacek; Rapacz‐Leonard, Anna; Wiącek, Dariusz; Kankofer, Marta; Janowski, Tomasz
Abstract: Protein profile of the placenta expresses its function and maintenance. Any alterations can be reflected in qualitative and quantitative changes in this profile. The aim of the present study was the evaluation of protein profile in the placenta of mares suffering from the retention of foetal membranes (FMR) by two separation methods and the comparison with physiologically released tissues. Placentas from 14 healthy, heavy draft mares were collected immediately after the expulsion of newborn. Tissues after homogenization and staining with fluorescent dyes were subjected to electrophoretic as well as chromatographic separation. Electrophoretic gels were statistically analysed for the presence and abundance of examined proteins, while some proteins were identified in chromatographic fractions. Out of 248 spots detected in endometrium, 38 differed significantly between FMR and control animals, while in allantochorion, respective values reached 241 and 27 spots ( p  < .05). Among identified proteins that expressed higher abundance in endometrium of FMR mares than control animals were prostaglandin reductase, dehydrogenase/reductase SDR family, and placental growth factor. These proteins are involved in regulation of parturition. Additionally, the following proteins responsible for physiological activity of a cell—guanine methyl transferase, aspartyl/asparaginyl beta‐hydroxylase and GTP‐binding protein, were identified. These proteins expressed higher abundance in allantochorion of FMR mares than in controls. This preliminary study confirmed the disturbances in protein pattern between foetal membranes in FMR and healthy mares. Further qualitative and quantitative experiments are necessary to deepen our knowledge on the mechanisms of the retention of foetal membranes in mares.